A COMPARISON OF MOOD STRUCTURES IN TWO TV TALK SHOWS WITH GUESTS OF DIFFERENT SOCIAL STATUS - Ae Mon Kyaw; Xin Zhiying; Vincent Mbahawa Chefor (Universitas Islam Sumatera Utara (UISU), 2020)
Language cannot be separated from the social context and culture. In everyday communication, people act and react differently depending on interactants, topics involved, and means of communication. This study, therefore, analyses two Talk Shows with guests of different power status- Ellen with Vice President Joe Biden and Ellen with Special Education teacher Jenna Albi. The analysis is carried out using Halliday’s Mood analysis framework, as revised by Matthiessen (2014) and Eggin (2004). The present study compares Ellen’s use of Mood structures and their functions in the interaction with different social beings. It reveals that in the talk with the Vice President, Ellen uses questions most (28.37%), followed by statements (20%) while in the talk with the Special Education teacher, Ellen prioritizes statements (43%) over questions (14%). On the other hand, she does not enjoy any Commands (0%) in the talk with the Vice President but does so with the teacher (18%). It turns out that, unlike in Fairclough’s (2001) finding, participants with high power status tend to answer questions rather than asking questions.